2017
DOI: 10.1002/2016pa003057
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Uncertainty in Estimating Lead/Lag Relationships in Marine Sedimentary Archives: A Case Study From the Tropical Pacific

Abstract: Understanding the mechanisms behind any changes in the climate system often requires establishing the timing of events imprinted on the geological record. However, these proxy records are prone to large uncertainties, which may preclude meaningful conclusions about the relative timing of events. In this study, we put forth a framework to estimate the uncertainty in phase relationships inferred from marine sedimentary records. The novelty of our method lies in the accounting of the various sources of uncertaint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 104 publications
0
10
0
Order By: Relevance
“…For age models generated either by δ 18 O alignment or radiocarbon dating, the amount of age uncertainty depends on the time resolution of the δ 18 O or 14 C data, respectively. A comparison of 15 low-latitude Pacific cores found that 14 C-based age uncertainty is comparable to, if not greater than, the uncertainty associated with δ 18 O alignments by HMM-Match (Khider et al, 2017).…”
Section: Age Modelsmentioning
confidence: 94%
“…For age models generated either by δ 18 O alignment or radiocarbon dating, the amount of age uncertainty depends on the time resolution of the δ 18 O or 14 C data, respectively. A comparison of 15 low-latitude Pacific cores found that 14 C-based age uncertainty is comparable to, if not greater than, the uncertainty associated with δ 18 O alignments by HMM-Match (Khider et al, 2017).…”
Section: Age Modelsmentioning
confidence: 94%
“…We note, however, that these records show variable ratios of productivity to dissolution as the main source of variance in the data. Future additional testing of phase uncertainties could include statistical approaches, such as Monte Carlo simulations (Khider et al, 2017).…”
Section: Evaluation Of Tuning Signalsmentioning
confidence: 99%
“…To determine the main long‐term trends in the δ 13 C DIC equivalent data for each region, we combined downcore δ 13 C G . bulloides TC data sets from the same region (e.g., BoP and NCR) using a Monte Carlo simulation in the program R, which considers the analytical and chronological errors to provide a statistically robust long‐term trend (Khider et al, ). For the analytical error for δ 13 C G .…”
Section: Methodsmentioning
confidence: 99%
“…Planktic δ 13 C are typically noisy and hard to interpret. To determine the main long-term trends in the δ 13 C DIC equivalent data for each region, we combined downcore δ 13 C G.bulloidesTC data sets from the same region (e.g., BoP and NCR) using a Monte Carlo simulation in the program R, which considers the analytical and chronological errors to provide a statistically robust long-term trend (Khider et al, 2017). For the analytical error for δ 13 C G.bulloides we used ±0.05‰ and all δ 13 C are reported with respect to the Vienna Peedee Belemite (vpdb) standard Schiraldi et al, 2014).…”
Section: Paleoceanography and Paleoclimatologymentioning
confidence: 99%